1986
DOI: 10.1073/pnas.83.20.7673
|View full text |Cite
|
Sign up to set email alerts
|

all-trans-Retinal stimulates superoxide release and phospholipase C activity in neutrophils without significantly blocking protein kinase C.

Abstract: ABSTRACTall-trans-Retinal was previously shown to stimulate high levels of superoxide release by guinea pig neutrophils. When the cells, previously labeled with [3H]inositol, are treated with all-trans-retinal, they exhibit a decrease in the levels of [3H]inositol phospholipids and an increase in the accumulation of [3H]inositol phosphates. The maximal accumulation of inositol phosphates and the optimal rate of superoxide release occurred together at -7 min after stimulation. Retinoids are known to block the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…NADPH oxidase has only recently been implicated as the enzymatic source of ROS generated in retinas exposed to bright light (30). Studies performed in neutrophils have demonstrated that atRAL acts as a potent stimulator of superoxide production through NADPH oxidase (33,34). In the present study, two structurally different NADPH oxidase inhibitors independently reduced ROS generation to levels similar to those in non-light exposed control mice and provided substantial protection against light-induced retinal degeneration in Abca4…”
Section: Rdh8mentioning
confidence: 54%
See 3 more Smart Citations
“…NADPH oxidase has only recently been implicated as the enzymatic source of ROS generated in retinas exposed to bright light (30). Studies performed in neutrophils have demonstrated that atRAL acts as a potent stimulator of superoxide production through NADPH oxidase (33,34). In the present study, two structurally different NADPH oxidase inhibitors independently reduced ROS generation to levels similar to those in non-light exposed control mice and provided substantial protection against light-induced retinal degeneration in Abca4…”
Section: Rdh8mentioning
confidence: 54%
“…NADPH oxidase is the primary catalyst involved in atRALstimulated superoxide production by neutrophils (33,34). To examine the role of NADPH oxidase in retinal cells, we added APO, a widely used NADPH oxidase inhibitor that interrupts NADPH oxidase complex assembly, to ARPE19 cells together with atRAL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lochner et al [14] have demonstrated that all-trans-retinol activates PI-specific phospholipase C in neutrophils and causes only a slight decrease in PKC activity. Ponec et al [15] showed no alteration in phospholipid turnover at 3 × 10 -6 M RA in squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%